The exception that proves the rule: how sodium chelation can alter the charge-cell binding correlation of fluorescein-based multimodal imaging agents - Maspero, Marco; Dallanoce, Clelia; Wängler, Björn; Wängler, Carmen; Hübner, Ralph (ChemMedChem, 2022)
Abstract In the present study we describe and explain an aberrant behavior in terms of receptor binding profile of a fluorescein-based multimodal imaging agent for gastrin releasing peptide receptor (GRPR) visualization by elucidating a chelating mechanism on sodium ions of its fluorescent dye moiety. This hypothesis is supported by both biological results and spectroscopic analyses of different fluorescein-carrying conjugates and an equally charged set of analogous tartrazine-based GRPR-binding imaging agents. Fluorescein interacts with sodium which reduces the overall negative charge of the dye molecule by one. This reduction in apparent total net charge explains the exceptional behavior found for the fluorescein-based multimodal bioconjugate in the context of the charge-cell binding correlation hypothesis.
Erstmals veröffentlicht: 09. Februar 2022
Gesehen am 19.03.2024